2005
DOI: 10.1073/pnas.0500307102
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid protects against secondary damage after spinal cord injury

Abstract: Peroxynitrite contributes to the pathogenesis of various neurodegenerative disorders through multiple mechanisms and is thought to mediate secondary neuronal cell death after spinal cord injury (SCI). Here we establish that physiologically relevant levels of uric acid (UA), a selective inhibitor of certain peroxynitrite-mediated reactions, block the toxic effects of peroxynitrite on primary spinal cord neurons in vitro. Furthermore, administration of UA at the onset of SCI in a mouse model inhibits several pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 62 publications
8
88
0
Order By: Relevance
“…The current results, as well as those of earlier studies (Bao et al, 2003; Genovese et al, 2007; Liu et al, 2005; Scott et al, 1999; Scott et al, 2003; Scott et al, 2005; Xiong et al, 2007; Xiong and Hall, 2009), suggest that the administration of antioxidants that target PN or PN-derived radicals within the first hours after SCI should provide effective neuroprotection. In agreement with this idea, compounds that can either scavenge peroxynitrite such as uric acid (Scott et al, 2005) or FeTSPP (Genovese et al, 2007), or its derived free radicals such as tempol (Hillard et al, 2004; Xiong and Hall, 2009) have been reported to attenuate post-SCI spinal tissue damage.…”
Section: Discussionsupporting
confidence: 74%
“…The current results, as well as those of earlier studies (Bao et al, 2003; Genovese et al, 2007; Liu et al, 2005; Scott et al, 1999; Scott et al, 2003; Scott et al, 2005; Xiong et al, 2007; Xiong and Hall, 2009), suggest that the administration of antioxidants that target PN or PN-derived radicals within the first hours after SCI should provide effective neuroprotection. In agreement with this idea, compounds that can either scavenge peroxynitrite such as uric acid (Scott et al, 2005) or FeTSPP (Genovese et al, 2007), or its derived free radicals such as tempol (Hillard et al, 2004; Xiong and Hall, 2009) have been reported to attenuate post-SCI spinal tissue damage.…”
Section: Discussionsupporting
confidence: 74%
“…By using complementary genetic approaches disrupting and overexpressing UOx, we have demonstrated that disruption of the UOx gene with a resultant rise in urate protects the nigrostriatal dopaminergic system, and conversely that transgenic overexpressson of UOx with a resultant fall in urate exacerbates dopaminergic neurodegeneration and resultant neurochemical and behavioral deficits in a 6-OHDA mouse model of PD. Neuroprotective effects of urate have been reported in various in vitro and in vivo experimental models of neurological disorders, including ischemic brain injury (13,14), multiple sclerosis (15), and spinal cord injury (16,17). However, evidence regarding urate in PD models is sparse and largely restricted to cellular models of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Urate is a potent antioxidant, and antioxidant properties of urate have been proposed to mediate its neuroprotective effects in most aforementioned studies (13)(14)(15)(16)(17)(18)(19)(20)(21). We investigated oxidative stress status in UOx KO and Tg mice and found higher protein carbonyls, one of the most commonly used markers of oxidative stress, in both.…”
Section: Discussionmentioning
confidence: 99%
“…Urate protected cultured spinal cord neurons from glutamate toxicity [37] and was neuroprotective in models of spinal cord injury, multiple sclerosis, brain injury, and stroke [38][39][40][41]56]. This growing literature suggests a potential neuroprotective role for urate beyond PD.…”
Section: Urate Is Neuroprotective In Several Preclinical Models Of Nementioning
confidence: 99%
“…Neuroprotective [35] Neuroprotective in SCI, brain ischemia/stroke, MS [38][39][40][41] Clinical trials SURE-PD (phase II trial) [10] URICO-ICTUS (phase IIb/III trial in stroke) [42,43] PD = Parkinson's disease; ALS = amyotrophic lateral sclerosis; AD = Alzheimer's disease; HD = Huntington's disease; MSA = multiple system atrophy; MCI = mild cognitive impairment; SCI = spinal cord injury; MS = multiple sclerosis …”
Section: In Vivomentioning
confidence: 99%